The impact of using a closed‐loop system on food choices and eating practices among people with Type 1 diabetes: a qualitative study involving adults, teenagers and parents. Issue 6 (29th January 2019) - Lawton, J.; Blackburn, M.; Rankin, D.; Allen, J.; Campbell, F.; Leelarathna, L.; Tauschmann, M.; Thabit, H.; Wilinska, M. E.; Hovorka, R.
Abstract: Aims: We explored whether, how and why moving onto and using a hybrid day‐and‐night closed‐loop system affected people's food choices and dietary practices to better understand the impact of this technology on everyday life and inform recommendations for training and support given to future users. Methods: Twenty‐four adults, adolescents and parents were interviewed before commencing use of the closed‐loop system and following its 3‐month use. Data were analysed thematically and longitudinally. Results: While participants described preparing and/or eating similar meals to those consumed prior to using a closed‐loop, many described feeling more normal and less burdened by diabetes in dietary situations. Individuals also noted how the use of this technology could lead to deskilling (less precise carbohydrate counting) and less healthy eating (increased snacking and portion sizes and consumption of fatty, energy‐dense foods) because of the perceived ability of the system to deal with errors in carbohydrate counting and address small rises in blood glucose without a corrective dose needing to be administered. Conclusions: While there may be quality‐of‐life benefits to using a closed‐loop, individuals might benefit from additional nutritional and behavioural education to help promote healthy eating. Refresher training in carbohydrate counting may also be necessary to help ensure that users are able to undertake diabetes management in situations where the technology might fail or that they take a break from using it. What's new?: This is the first study to explore how moving onto and using a closed‐loop system may affect people's food choices and eating practices. Using a closed‐loop can help people to feel more normal, and less anxious and burdened by diabetes in dietary situations. While we did not find the level of unrestrained eating behaviour hypothesized by others, we did observe some potential slippage into increased snacking and unhealthier eating as a result of using a closed‐loop. We support recommendations for people to be given tailored training and nutritional support to help promote healthy eating while using a closed‐loop.